Clinical application of two-port laparoscopic surgery in sigmoid colon and upper rectal cancer resection - Jiang, Feng; Ji, Mengmeng; Jin, Fangtong; Liu, Junfeng; Liu, Xiaoping (Frontiers in Oncology, 2023)
Background: In the field of minimally invasive surgery, the two-port laparoscopic surgery is on the rise. This study investigated the safety and efficacy of two-port laparoscopic surgery (TLS) for resecting sigmoid colon and upper rectal cancers compared with conventional laparoscopic surgery (CLS).The clinical data of patients undergoing laparoscopic sigmoid colon cancer and upper rectal cancer resection at the Department of General Surgery of the First Affiliated Hospital of Gannan Medical College between July 2019 and January 2022 were retrospectively collected. Grouped according to different laparoscopic surgery.Based on the inclusion and exclusion criteria,A total of 81 patients were enrolled, of the 25 patients from the TLS group,and of the 56 patients from the CLS group.We mainly compared whether there were statistical differences between the two groups in terms of operative time, intraoperative bleeding, incision length, time to first ambulation, time to first flatus, time to first defecation, postoperative complication rate, and other surgical outcomes.Results: There was no statistical difference between the two groups in terms of baseline clinical characteristics (P > 0.05). In terms of the surgical outcomes, there were statistical differences in the total incision length (TLS: 6.21 ± 0.67 cm, CLS: 8.64 ± 1.08 cm, P < 0.001)), time to first ambulation (TLS: 2.0 ± 0.7 d, CLS:3.1 ± 0.9 d, P < 0.001), time to first flatus (TLS: 2.5 ± 0.8 d, CLS: 3.0 ± 0.8 d, P = 0.028), time to first defecation (TLS: 3.8 ± 1.3 d, CLS: 5.1 ± 2.1 d, P = 0.010), and time for liquid diet (TLS: 4.3 ± 1.4 d, CLS: 5.3 ± 1.9 d, P = 0.021). There was no statistical difference between the two groups in terms of the pathology (P > 0.05).In terms of safety, TLS in sigmoid colon and upper rectal cancer resection is comparable to CLS. However, its incision is smaller and more aesthetic, and it causes lesser trauma than CLS. Additionally, it is also superior to traditional laparoscopy in postoperative recovery.